2014
DOI: 10.1002/14651858.mr000035.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Bias due to selective inclusion and reporting of outcomes and analyses in systematic reviews of randomised trials of healthcare interventions

Abstract: Discrepant outcome reporting between the protocol and published systematic review is fairly common, although the association between statistical significance and discrepant outcome reporting is uncertain. Complete reporting of outcomes in systematic review abstracts is associated with statistical significance of the results for those outcomes. Systematic review outcomes and analysis plans should be specified prior to seeing the results of included studies to minimise post-hoc decisions that may be based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(93 citation statements)
references
References 93 publications
1
88
0
1
Order By: Relevance
“…57 There is also evidence that those reporting on primary studies might choose to play down the estimates of harms and emphasise the efficacy of the intervention instead. [56][57][58] Selective outcome reporting and publication bias (where entire studies are unpublished due to the unexpected findings of harms) could therefore work in different directions from that observed with efficacy trials where benefits are emphasised and harms are neglected or distorted. 4 56-63 When statistical approaches are used to probe for the possibility of biased reporting, they should be explicitly described and used with caution.…”
Section: Recommendations For Reporting Harms In Systematic Reviewsmentioning
confidence: 99%
“…57 There is also evidence that those reporting on primary studies might choose to play down the estimates of harms and emphasise the efficacy of the intervention instead. [56][57][58] Selective outcome reporting and publication bias (where entire studies are unpublished due to the unexpected findings of harms) could therefore work in different directions from that observed with efficacy trials where benefits are emphasised and harms are neglected or distorted. 4 56-63 When statistical approaches are used to probe for the possibility of biased reporting, they should be explicitly described and used with caution.…”
Section: Recommendations For Reporting Harms In Systematic Reviewsmentioning
confidence: 99%
“…The intention is to reduce the risk of bias related to selective reporting by stating a priori hypotheses and methods explicitly [18]. However, a thorough evaluation should focus on discrepancies between the protocol and the final review, which research has shown to be fairly common [19, 20]. It is not sufficient only to refer to a protocol, therefore, as this would primarily reflect the quality of reporting.…”
Section: Discussionmentioning
confidence: 99%
“…The ‘obsession’ with articles attracting abundant citations may be also the trigger of the current unprecedented proliferation of systematic reviews (14), most of which are of low quality and even harmful for the scientific evidence accumulation (151617). …”
Section: Misusesmentioning
confidence: 99%